ANALISIS PENERAPAN GREEN TRANSPORTATION DI KOTA PALEMBANG - Rahmadona, Efrilia; Ruliansyah, Hafiz; Widjaya, M. Fadil Yulian; Panca P, M. Sang Gumilar; Bonardo, Cahyadi; Purniawan, Bandi (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2024)
Electric cars have significant potential to be implemented in Palembang city, which is committed towards smart city with a focus on ‘smart mobility.’ This study explores the characteristics of electric car users and their operational cost efficiency compared to petrol vehicles. Using a quantitative method with a questionnaire, data was collected from 104 respondents and showed that the majority of electric car users are men aged 20-30 years old with an income of 5-10 million. The results of the analysis show that the operating costs of electric vehicles are more economical compared to conventional vehicles. However, there are challenges such as limited charging infrastructure and higher electric car prices. Through SWOT analysis with the IFAS EFAS method, this study was identified as being in quadrant 2 with a tendency towards weakness where the application requires selective maintenance, meaning that the application of electric cars requires action to improve and enhance several aspects, aspects that need to be improved by recommending actions such as reducing the price of electric cars, providing more charging stations, and increasing public awareness about the use of environmentally friendly electric cars so as to encourage wider adoption in Palembang.